Galactagogue effect of banana (Musa x paradisiaca) blossom beverage on breast milk production among mothers undergoing cesarean section. - Susanha Yimyam; Sunisa Pattamapornpong (Nursing and Health Sciences Journal (NHSJ), 2022)
There is limited evidence to support the effectiveness of banana blossom in promoting breast milk supply among mothers undergoing cesarean section. To investigate the clinical galactagogue effect of banana blossom on breast milk production among mothers undergoing cesarean section. A randomized controlled trial was conducted with the experimental group (ne=30) who consumed banana (Musa X paradisiaca) blossom beverage and the control group (nc=30) who consumed plain water. The results showed that mothers undergoing cesarean section in the experimental group had significantly higher milk flow levels at Day 2 (P = 0.017), Day 3 (P = 0.005) and milk volume at Day 2 (P = 0.005), and Day 3 (P = <0.001) than those of control group. This study had proven the galactagogue effect of banana blossom beverage to promote breast milk production, without any notable adverse effect. It could be used to be the alternative daily menu for postpartum mothers and a solution for midwives to deal with those who have inadequate production of breast milk.